2018
DOI: 10.3390/cells7080085
|View full text |Cite
|
Sign up to set email alerts
|

Coagulation, Microenvironment and Liver Fibrosis

Abstract: Fibrosis is the main consequence of any kind of chronic liver damage. Coagulation and thrombin generation are crucial in the physiological response to tissue injury; however, the inappropriate and uncontrolled activation of coagulation cascade may lead to fibrosis development due to the involvement of several cellular types and biochemical pathways in response to thrombin generation. In the liver, hepatic stellate cells and sinusoidal endothelial cells orchestrate fibrogenic response to chronic damage. Thrombi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 141 publications
(157 reference statements)
0
33
0
Order By: Relevance
“…High VWF levels indicate endothelial dysfunction and liver sinusoidal endothelial cells (LSEC) likely contribute to the increased VWF levels in these patients 39 . LSEC dysfunction impacts intrahepatic resistance, and thus, aggravates portal hypertension, which may further increase bacterial translocation 40 .…”
Section: Discussionmentioning
confidence: 99%
“…High VWF levels indicate endothelial dysfunction and liver sinusoidal endothelial cells (LSEC) likely contribute to the increased VWF levels in these patients 39 . LSEC dysfunction impacts intrahepatic resistance, and thus, aggravates portal hypertension, which may further increase bacterial translocation 40 .…”
Section: Discussionmentioning
confidence: 99%
“…The activation of hepatic stellate cells (HSC) is the key pathogenic mechanism of hepatic fibrogenesis. Experimental animal models support a biological link between coagulation and fibrosis showing that thrombin and FXa can activate HSC [62,63] and, conversely, their inhibition by anticoagulants may prevent or reduce fibrogenesis [57].…”
Section: Potential Role Of Coagulation System On the Development Of Tmentioning
confidence: 99%
“…While currently available direct-acting antivirals will probably erase the burden of chronic viral hepatitis, effective antifibrotic drugs for CLD are still lacking [62]. Patients with metabolic disease (NAFLD/NASH) with indication to anticoagulation are continuously rising and would represent the ideal candidates for future studies evaluating the effect of long-term anticoagulation, including DAOCs, on fibrogenesis and portal hypertension.…”
Section: Potential Role Of Coagulation System On the Development Of Tmentioning
confidence: 99%
“…255 The cellular responses of thrombin are mediated by receptors with proteolytic activity-protease-activated receptors (PAR), expressed by endothelium, platelets, and HSCs enable crosstalk between these cells. 256,257 Thrombin exerts vasoconstricting, proinflammatory, and prohemostatic effects and also promotes proliferation and a profibrotic phenotype of HSCs. 258,259 Thus, inhibition of PARs is a promising therapeutic target in liver fibrosis and PHT, since experimental studies showed that inhibition of PARs prevents the fibrogenic response of HSCs in animal models of liver diseases.…”
Section: Anticoagulationmentioning
confidence: 99%